Multidisciplinary tumor board for head and neck cancer from the perspective of medical oncologists—optimizing its effectiveness - Yokota, Tomoya; Mukaigawa, Takashi; Yasunaga, Yoshichika; Ogawa, Hirofumi; Onoe, Tsuyoshi; Yurikusa, Takashi; Yamashita, Aiko (Frontiers in Oncology, 2023)
Head and neck cancer (HNC) treatment is becoming increasingly multidisciplinary, and patient characteristics vary. Therefore, a multidisciplinary tumor board (MTB) is essential in clinical practice. This review provides insights into the benefits and tips for improving head and neck MTB from the perspective of medical oncologists. The MTB is a platform to discuss the optimal application of the standard of care to each case, reach a consensus, and establish a recommendation to support patients’ decision-making. A productive and educational MTB also provides an opportunity to share information on ongoing clinical trials with physicians. Case presentations should be systematic to discuss all new and challenging cases before, during, and after the treatment. Human resource development, particularly of head and neck medical oncologists, is crucial. The type of multidisciplinary network between medical staff and the extent of patient intervention differs among MTB teams. Subsequently, a virtual MTB can establish a medical network between institutions that will contribute to the equalization and centralization of head and neck oncologic care.